Development and demonstration of novel cryogenic distillation process for offshore gas platform - Kim, Y. (Offshore Technology Conference, 2019)
Natural gas consists of methane and other gases, which are mostly natural gas liquid (NGL), CO2, H2S and water. NGL generally refers the stream containing C2 or heavier hydrocarbons, mostly ethane and propane 5. The recovery of C2+ components from the sale gas can enhance cost-effectivness in natural gas processing by selling highly valuable feedstocks for petrochemical sectors. The schematic block diagram for the cryogenic distillation process widely-used in the offshore environments, is illustrated in Figure 1. Feed gas is pre-cooled before being separated in the distillation column operated cryogenic conditions. J-T valves or turboexpanders are commonly used for the expansion of gas stream which is introduced for providing necessary cooling or cold condition required for the process, while a compander may be applied to increase energy efficiency. The turboexpander-based cryogenic distillation process has been the most widely used for extracting NGL from natural gas because of its high energy efficiency and ethane recovery performance, compared to other processes 15. Various process configurations for turbo-expander processes have been developed for improving energy efficiency or ethane recovery or adaptability 11, 13, which includes: Gas Subcooled Process (GSP) Cold Residue Reflux process (CRR) Recycle Split Vapor process (RSV) Single Column Overhead REcycle (SCORE) Although there are differences in the configurations, in terms of heat recovery, power recovery and interconnectivity between streams, the unit operations and their sequences required for the NGL recovery through cryogenic distillation is more or less the same. Copyright Â© 2019, Offshore Technology Conference